Multistable Soft Robots Assembled from Bistable Auxetic Building Blocks - Bojian Zhang; Zhiqiang Meng; Xudong Yang; Yiran Zhang; Tianyu Chen; Yu Chen; Yifan Wang (Advanced Intelligent Systems)
Soft robotics have significantly influenced both scientific and industrial domains over the past decades. However, their inherent limitations of material or structural softness pose a persistent challenge in terms of shape retention and load capacity for various applications. To address this challenge, bistable and multistable structures with two or more mechanically stable states and snap‐through switchability emerge as a promising solution. Herein, a multistable soft robot design assembled from bistable auxetic building blocks with negative Poisson's ratio and a large volumetric change is presented. The bistable mechanical behavior and optimal structural parameters have been investigated by mechanical modeling, finite element analysis, and experimental testing. To demonstrate the shape retention ability and enhanced load capacity of our robotic design, a multistable manipulator with a low‐complexity closed‐loop control system is presented, capable of maintaining 216 discrete stable states even when the pneumatic pressure supply is removed. To validate the multifunctionality of design, a multistable tube crawler with a notable load capacity of approximately five times its own body weight is developed.